MULTICULTURALISM AND SUBCULTURAL IN INDONESIA GENERAL ELECTION 2019 - Riswandi - Riswandi (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
The issue of multiculturalism and subcultural are developing in the even of Indonesian election in 2019 such as democracy, equality in the fields of law, social, political, and cultural, human rights, honesty, justice, political choice, and unfair legal enforcement, so that people tend to split. The problem of this research is what are the cultural perceptions of the Jakarta multicultural community toward the events of the 2019 Election?The case studied was 2019 Elecion and primary data was obtained through interview with 8 informants from Javanese, Batak, Sundanese, Bugis, Chinese, and Betawi subculturs, then confirm by intercultural communication experts, Alo Liliweri. Data were analyzing using Miles and Hubermans models.The result showed that the cultural perception of Jakarta multicultural community was based on subcultural perception, in which Javanese, Batak, and Chinese subcultures tended to support Jokowi, while the Sunda, Betawi, and Bugis subcultures tended to support Prabowo. Nonverbal behavior of subcultural member s regarding 2019 election is oriented towards Dominant Cultures or Indonesian National Culture as parta of Eastern Culture, and also influenced by their family background, profession and personal character.